2017
DOI: 10.1002/dc.23695
|View full text |Cite
|
Sign up to set email alerts
|

Cytological evaluation by fine needle aspiration biopsy of incidental focal increased fluorodeoxyglucose uptake in thyroid on positron emission tomography scan

Abstract: Malignancy was identified in 50% of the PET-positive incidentalomas in our series. PTC constitutes the major malignant diagnosis. No diagnostic value of SUV was observed to differentiate malignant from benign lesions. Diagn. Cytopathol. 2017;45:501-506. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…8 A study of >10,000 FDG PET/CT scans showed a rate of 1.7% incidental thyroid findings and a 33% malignant rate of these findings, agreeing with our findings, while a study of 20 thyroid incidentalomas showed a malignancy rate of 50%. 9,10 Of 12 lung findings, 2 (16.7%) were also ultimately malignant. This agrees with the 4% to 15% quoted in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…8 A study of >10,000 FDG PET/CT scans showed a rate of 1.7% incidental thyroid findings and a 33% malignant rate of these findings, agreeing with our findings, while a study of 20 thyroid incidentalomas showed a malignancy rate of 50%. 9,10 Of 12 lung findings, 2 (16.7%) were also ultimately malignant. This agrees with the 4% to 15% quoted in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the widespread use of ultrasound as well as the increasing number of imaging studies performed for reasons other than planned assessment of the thyroid gland (i.e., computed tomography of the chest or cervical spine, magnetic resonance imaging of the cervical spine, and whole-body positron emission tomography), incidental thyroid nodules (TNs) ≤ 10 mm are now common findings [1][2][3][4][5]. The characterization of TNs has improved because of better ultrasound image resolution and the introduction of new diagnostic ultrasound tools such as elastography [6].…”
Section: Introductionmentioning
confidence: 99%
“…All studies but one [ 29 ] were reported in the English language. Nine studies were performed by Asian/Eastern [ 17 20 , 22 24 , 27 , 31 ] and six by Western [ 21 , 25 , 26 , 28 30 ] authors. They were single-center or observational cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence in the BETHESDA subcategories was substantially unchanged (I 12%, II 47%, III 6%, IV 4%, V 6%, and VI 21%) and the inconsistency remained high (detailed data not shown). A second analysis was performed considering separately the nine studies from Asian/Eastern countries [ 17 20 , 22 24 , 27 , 31 ] and the six studies from Western authors [ 21 , 25 , 26 , 28 30 ] as shown in Table 4 . There was a significantly different prevalence in the BETHESDA category IV between Asian/Eastern and Western studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation